The Relationship between Neonatal Jaundice and Maternal and Neonatal Factors - Ehsan Garosi; Fatemeh Mohammadi; Fatemeh Ranjkesh (Mashhad University of Medical Sciences, 2016)
Background: Maternal and neonatal factors could help determine the potential incidence of hyperbilirubinemia. In this study, we aimed to identify the relationship between the severity of jaundice in newborns and maternal and neonatal factors. Methods: This descriptive, cross-sectional study was conducted in 2014. Icteric newborns, admitted to Qods and Kowsar teaching hospitals in Qazvin, Iran were recruited in the study. Data were collected, using a researcher-made checklist consisting of three parts: demographic, maternal, and neonatal information. For data analysis, statistical tests including t-test, Mann-Whitney, analysis of variance, and Pearson's correlation test were performed, using SPSS version 19. Results: The results showed that the mean total bilirubin level was significantly higher in newborns delivered vaginally (17.3±3.5 mg/dl), compared to cases born by cesarean section (16.1±3.9 mg/dl) (P=0.02). Also, the mean total and direct bilirubin levels were higher in neonates delivered using oxytocin (0.4±.1 and 17.99±0.4, respectively), compared to those without oxytocin induction (0.383±0.1 and 16.2±0.28, respectively) (P=0.001). Moreover, the mean total and direct bilirubin levels were higher among female newborns (0.397±0.013 and 17.2±0.29, respectively), compared to the male neonates (0.379±.22 and 15.9±0.37, respectively) (P=0.005 and P=0.02, respectively). Conclusion: Since factors such as mode of delivery, oxytocin induction, and neonate's gender could contribute to jaundice, continuous assessment of newborns after birth could facilitate early diagnosis, promote disease management, and reduce the subsequent complications.